Development of Student Islamic Behavior Through Worship Practice Activities at SMAN City of Bandung - Iha Hamidah; Agus Salim Mansyur; Supiana Supiana; Erihadiana Erihadiana (Journal of Social Science, 2021)
This study aims to describe the development of Islamic behavior of students through the practice of worship at SMAN Bandung. Based on observations and interviews of researchers to several principals of SMAN schools in Bandung who have athlete students, found that not all students who profess to be Muslim to perform worship well during sports practice while in school, only some students who want to perform worship in school, such as performing sunnah prayers or obligatory prayers in school mosques , on the grounds that his clothes are dirty because of sweat, responsibility is training and clashing with training time. Whereas if praying his clothes must be clean and holy. Sometimes, even many students have not prayed if they are not ordered and many others lack. Not infrequently students who when at home and at school show good Islamic behavior, but when outside the house and outside the school shows bad behavior seen in terms of Islam, such as smoking, hanging out on the side of the road, and excessive dating. This study uses qualitative approach with descriptive method. Data collection techniques through interviews, observations, and documentation. Data analysis techniques use data analysis techniques consisting of data reduction, data presentation, and drawing conclusions. The results of this study are: 1) Islamic behavior development program in high school in Bandung, namely congregational prayers before the start and at the end of teaching and learning activities, memorizing Asmaul Husna, reading the Quran 15 minutes before the first hour. 1) learning begins, praying dhuha congregation, praying midday congregation, infaq or setting aside some pocket money for alms. 2) The process of fostering islamic keisk behavior of students through religious practice activities in SMAN throughout Bandung needs to be held, religious lectures, guidance and supervision. 3) The behavior of students after receiving guidance through the practice of worship in SMAN throughout The City of Bandung is quite good. Students can be responsible and disciplined in performing worship. Students can also work together and socialize well.